A weak form quadrature element formulation for coupled analysis of unsaturated soils. (June 2016) - Yuan, Shuai; Zhong, Hongzhi
Abstract: A weak form quadrature element formulation is proposed for coupled analysis of unsaturated soils. In the formulation, integration points are coincident with nodes where all variables are obtained so that numerical implementation is made easy. Accuracy can be improved by the increase of the approximation order. An elasto-plastic constitutive model is used for description of the mechanical behavior, and hydraulic hysteresis of the soil water characteristic curve is considered. Results are compared with available analytical solutions, experimental data and numerical solutions in the literature, and good agreement is reached. Rapid convergence is reached as compared with the conventional finite element method. The effect of the ground water level is discussed.